THE EFFECT OF PROTECTION FILM ON THE ADAPTATION OF ‘HANFU’ APPLE TREES UNDER LOW TEMPERATURE - X. Zhang; H. Ma; D. Lü; S. Qin; G. Du; G. Liu (Journal of Animal and Plant Sciences, 2015)
In this study, ‘Hanfu’ apple trees were used as a test material to determine the effect of a functional protective film on the ability of the trees to withstand temperatures below zero. The functional protective film is a quaternary copolymer prepared by emulsion polymerization of vinyl acetate (Vac), butyl acrylate (NbA), methyl methacrylate (MMA) and acrylic acid (AA). The resulting copolymer was modified by adding a thermal insulation material (ceramic powder) to enhance the insulating properties of the film. Compared with a control, application of various quantities of the protective film resulted in as much as 2.5℃ decrease in the semi lethal temperature for ‘Hanfu’ trees. The insulating protective coating effectively reduced the MDA (malondialdehyde) content and significantly increased the activities of antioxidant- enzyme in the tree branches, which improved the low-temperature adaptability of the plants helping them to maintain normal physiological functioning. In the four treatments, protective films with the addition of 4% and 6% thermal insulation offered better protective effects
Keywords: Protection film; Thermal insulation; ‘Hanfu’ Apple; Low-temperature stress; Semi lethal temperature